2021
DOI: 10.1007/s10489-021-02193-w
|View full text |Cite
|
Sign up to set email alerts
|

Using artificial intelligence techniques for COVID-19 genome analysis

Abstract: The genome of the novel coronavirus (COVID-19) disease was first sequenced in January 2020, approximately a month after its emergence in Wuhan, capital of Hubei province, China. COVID-19 genome sequencing is critical to understanding the virus behavior, its origin, how fast it mutates, and for the development of drugs/vaccines and effective preventive strategies. This paper investigates the use of artificial intelligence techniques to learn interesting information from COVID-19 genome sequences. Sequential pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 62 publications
0
36
0
Order By: Relevance
“…The gene coding region, also recognized as the CDS (coding sequence), is the part of a gene's DNA or RNA that is coded for protein. 5 To find the coding regions CDS in the Fig. 5 Composition of amino acids Fig.…”
Section: Genome Sequence Analysis Of Covid-19 and Alike Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene coding region, also recognized as the CDS (coding sequence), is the part of a gene's DNA or RNA that is coded for protein. 5 To find the coding regions CDS in the Fig. 5 Composition of amino acids Fig.…”
Section: Genome Sequence Analysis Of Covid-19 and Alike Virusesmentioning
confidence: 99%
“…Even though it is usually a tedious and resource-intensive procedure that mostly depends on field expertise. Various strains of the initial genome sequencing of COVID-19 did not set timely actionable discernments, yet many features of disease behavior are unknown [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 54 Proposed a genome analysis of COVID‐19 by using the AI. 58 Both chest x‐ray images and CT scan based automatic detection of corona virus is presented in References 59 , 60 , 61 . For analysis and detection of coronavirus a DL model is presented by Kedia et al 62 In the field AI and ML, TL is the most important and extensively used methodology that works based on previously trained ML models and re‐use the relevant knowledge of these trained models to different tasks.…”
Section: Related Workmentioning
confidence: 99%
“…In a recent study, confirmed COVID-19 cases of a few European countries, e.g., Denmark, Belgium, Germany, etc., were modeled and estimated by ARIMA, NARNN (Nonlinear Autoregression Neural Network) and LSTM (Long-Short Term Memory) approaches, respectively [ 26 ]. Besides, artificial intelligence techniques are used to learn interesting information and patterns from COVID-19 genome sequences [ 27 ]. As the COVID-19 disease spreads worldwide and the regional resilience requirement rises, daily-level regional data are needed for a detailed analysis and forecasting, e.g., population mobility, smoking rate, and the number of hospitals.…”
Section: Introductionmentioning
confidence: 99%